Problems in Physical Education in the Free Learning Curriculum - Zalikal Ilham (Tadulako Journal Sport Sciences And Physical Education, 2023)
Faced with current problems, in addition to facilities and infrastructure, there are still many children of the nation who have low moral awareness, not to mention the insight or experience of teachers in independent learning, therefore Indonesia needs to turn to education that provides moral values and builds strong character, one of which is PJOK, in the Ministry of Education and Culture Regulation of the Republic of Indonesia No. 24 of 2007 relating to facilities and infrastructure standards. In the era of global competition, developing from time to time and space, quality education is needed. Quality education that is able to answer the challenges of change and bring about changes in various dimensions of life. To guarantee the achievement of these goals, good insight from the teacher is needed so that in this independent learning the teacher has the opportunity to shape the character of students and to support this requires good facilities and infrastructure.